2013
DOI: 10.1371/journal.pone.0077589
|View full text |Cite
|
Sign up to set email alerts
|

Fish and Robots Swimming Together in a Water Tunnel: Robot Color and Tail-Beat Frequency Influence Fish Behavior

Abstract: The possibility of integrating bioinspired robots in groups of live social animals may constitute a valuable tool to study the basis of social behavior and uncover the fundamental determinants of animal functions and dysfunctions. In this study, we investigate the interactions between individual golden shiners (Notemigonus crysoleucas) and robotic fish swimming together in a water tunnel at constant flow velocity. The robotic fish is designed to mimic its live counterpart in the aspect ratio, body shape, dimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 76 publications
(76 reference statements)
1
61
0
1
Order By: Relevance
“…During interactions with a robot, visual information plays an important role (e.g., Faria et al, ). In particular, shape (e.g., Abaid, Bartolini, Macrì, & Porfiri, ; Polverino and Porfiri ) and color (e.g., Göth & Evans ; Polverino, Phamduy, & Porfiri, ) appear to be crucial in mediating interactions with robots in many species. Movement patterns (Göth & Evans ), particularly responsiveness toward another's movement (Kopman, Laut, Polverino, & Porfiri, ; Polverino, Phamduy, & Porfiri, ), also play a key role.…”
Section: Perception Of Robotsmentioning
confidence: 99%
“…During interactions with a robot, visual information plays an important role (e.g., Faria et al, ). In particular, shape (e.g., Abaid, Bartolini, Macrì, & Porfiri, ; Polverino and Porfiri ) and color (e.g., Göth & Evans ; Polverino, Phamduy, & Porfiri, ) appear to be crucial in mediating interactions with robots in many species. Movement patterns (Göth & Evans ), particularly responsiveness toward another's movement (Kopman, Laut, Polverino, & Porfiri, ; Polverino, Phamduy, & Porfiri, ), also play a key role.…”
Section: Perception Of Robotsmentioning
confidence: 99%
“…This model is often used to characterize the motion of live fish as well as to implement the same motion into bioinspired robotic fish [19], [30], [32], [33]. The sinusoidal amplitude, period, and phase offset parameters for each servomotor are derived from this model and then programmed into the microcontroller inside the robotic fish.…”
Section: Fish Tailmentioning
confidence: 99%
“…Therein, the speed of the robotic fish is measured as its swims according to the carangiform model [19], [30], [32], [33].…”
Section: Manual Modementioning
confidence: 99%
“…A variety of biologically-inspired robotic fish have been designed to mimic live species, including mosquitofish (Polverino and Porfiri 2013, b) and zebrafish (Abaid et al 2012;Butail et al 2013Butail et al , 2014Polverino and Porfiri 2013;Spinello et al 2013). While these prototypes mimicked several morphophysiological features of their live counterparts, their size was at least three times larger, thereby constituting a potential experimental confound in the analysis of sociality.…”
Section: Introductionmentioning
confidence: 99%
“…Although these approaches provide a feasible solution to miniaturize the robotic fish size, they are limited in their capability to provide multisensory cues, often associated with both visual and pressure stimuli. Beyond the demonstrated influence of pressure cues on the interaction between robots and live fish (Marras and Porfiri 2012;Polverino et al 2013), visual cues from the tail beating have been found to be a critical factor in the spatial preference toward robotic fish (Abaid et al 2012).…”
Section: Introductionmentioning
confidence: 99%